Data Hiding In Encrypted Video Stream By Code-Word Substitution - Hajare, Sagar; Nikam, Sujata; Vispute, Kavita; Bodke, Ravindra (International Journal of Computer Sciences and Engineering, 2025)
Inspired by the SMVQ technique, this dissertation proposes a reversible data hiding based on VQ-compressed images.This scheme can completely recover the original VQ cover image from an embedded image after the embedded message is extracted. Compared to the SMVQ technique that is very time consuming to set up a state codebook and then search the nearest codeword, the proposed scheme employs block match coding (BMC) to reduce the complexity and preserve a satisfactory embedding capacity. The main problems in the former works are low embedding capacities, low embedding rates, high complexities, or high bit rates. To improve these problems, the proposed scheme applies the BMC prediction to encode indices, and thus can obtain a higher embedding capacity, higher embedding rate, higher processing efficiency, and lower bit rate simultaneously. This chapter describes the method used for data hiding that is vector quantization and its type side match vector quantization in detail.